First record of Enochrus (Lumetus) hamiltoni from Cuba (Coleoptera: Hydrophilidae) with notes on its habitat - DELER-HERNÁNDEZ, ALBERT; DELGADO, JUAN A. (Revista Colombiana de Entomología, 2010)
Enochrus (Lumetus) hamiltoni (Coleoptera, Hydrophilidae) is recorded for the first time from the island of Cuba. This aquatic beetle has been collected in two coastal localities from the southeast of the island in two brackish systems of temporal ponds, non eutrophic, with muddy bottoms and permanent exposure to the sun. Some specimens were collected associated with the vegetation, both emergent and submergent, at the margins of these ponds.